Effect of needle length on incidence of local reactions to routine immunisation in infants aged 4 months: randomised controlled trial. Issue 7266 (14th October 2000) - Diggle, Linda; Deeks, Jonathan
Abstract: Objective: To compare rates of local reactions associated with two needle sizes used to administer routine immunisations to infants. Design: Randomised controlled trial. Setting: Routine immunisation clinics in eight general practices in Buckinghamshire. Participants: Healthy infants attending for third primary immunisation due at 16 weeks of age: 119 infants were recruited, and 110 diary cards were analysed. Interventions: Immunisation with 25 gauge, 16 mm, orange hub needle or 23 gauge, 25 mm, blue hub needle. Main outcome measures: Parental recordings of redness, swelling, and tenderness for three days after immunisation. Results: Rate of redness with the longer needle was initially two thirds the rate with the smaller needle (relative risk 0.66 (95% confidence interval 0.45 to 0.99), P=0.04), and by the third day this had decreased to a seventh (relative risk 0.13 (0.03 to 0.56), P=0.0006). Rate of swelling with the longer needle was initially about a third that with the smaller needle (relative risk 0.39 (0.23 to 0.67), P=0.0002), and this difference remained for all three days. Rates of tenderness were also lower with the longer needle throughout follow up, but not significantly (relative risk 0.60 (0.29 to 1.25), P=0.17). Conclusions: Use of 25 mm needles significantly reduced rates of local reaction to routine infant immunisation. On average, for every five infants vaccinated, use of the longer needle instead of the shorter needle would prevent one infant from experiencing any local reaction. Vaccine manufacturers should review their policy of supplying the shorter needle in vaccine packs.